Brachial thromboembolectomy and retrograde innominate artery stenting in acute limb ischemia - Rachel Bernardo, BS; Hamda Almaazmi, MD; Shawn Sarin, MD, MBA; Salim Lala, MD, MBA, FACS, FRCSI (Journal of Vascular Surgery Cases and Innovative Techniques)
Acute limb ischemia is a critical vascular emergency often resulting from embolic sources, requiring prompt intervention to prevent significant morbidity and mortality. This paper presents a case of a 74-year-old female with acute limb ischemia due to a thromboembolus in the distal brachial artery and a nonocclusive mobile thrombus in the innominate artery. The patient underwent urgent brachial artery thromboembolectomy and subsequent retrograde innominate artery stenting via right open transcarotid approach. The retrograde approach was chosen to minimize stroke risk associated with embolization. The successful resolution of the arterial thrombus and restoration of arterial patency underscore the importance of individualized management strategies in complex vascular emergencies.